O processo de internacionalização do currículo em uma IES brasileira - Silva, Carla Camargo Cassol da (2022)
Driven by global society and its adjacent needs, the internationalization of education has become a central issue in discussions on the contribution of higher education institutions (HEIs) and the quality of education. Considering that the main mission of higher education to society is the development of professionals and citizens to live and work in a multicultural and interconnected world, a higher education institution that is not minimally internationalized cannot be considered excellent. Therefore, given the challenge of designing and promoting experiences that will purposefully develop global and intercultural competencies in students to promote the knowledge, skills and selfawareness they need to participate effectively as citizens and professionals in this global society, the internationalization of the curriculum appears as a viable alternative. The goal of this study is to propose the internationalization of the formal curriculum of an undergraduate program in a Brazilian HEI, based on Leask’s internationalization of the curriculum model (2015), following the action research protocols. Leask’s model (2015) was applied, with the involvement of professors and leaders from the HEI under study. Data were collected and analyzed during the research planning and execution phases. After the delivery of the internationalized curriculum proposal, an in-depth study, comprising the analyses previously carried out, the comparison of the current curriculum with the proposed one and a critical evaluation of the research process, made it possible to point out the research outcomes. In addition to the proposal of an internationalized formal curriculum for an undergraduate program, the research findings pointed to the need to adapt Leask’s model (2015) in the context under study. Such adaptions were made and analyzed, thus enabling the proposal of a new adapted model, which can be replicated in the Brazilian context, paving the way to internationalize more programs.